Body composition changes among female NCAA division 1 athletes across the competitive season and over a multiyear time frame - Stanforth, P. R.; Crim, B. N.; Stanforth, D.; Stults-Kolehmainen, M. A. (The Journal of Strength and Conditioning Research, 2014)
Body composition can affect athletic performance. Numerous studies have documented changes in body composition in female collegiate athletes from pre- to postseason; however, longitudinal studies examining changes across years are scarce. Therefore, the primary purpose of this study was to assess longitudinal body composition changes among female collegiate athletes across 3 years. Two hundred twelve female athletes from basketball (BB; n = 38), soccer (SOC; n = 47), swimming (SW; n = 52), track (sprinters and jumpers; TR; n = 49), and volleyball (VB; n = 26) with an initial mean age of 19.2 ± 1.2 years, height of 172.4 ± 8.9 cm, and total mass of 66.9 ± 9.0 kg had body composition assessments using dual-energy x-ray absorptiometry pre- and postseason over 3 years. A restricted maximum-likelihood linear mixed model regression analysis examined body composition differences by sport and year. Changes (p < 0.05) over 3 years included the following: Lean mass increased in VB from year 1 to 2 (0.7 kg), year 2 to 3 (1.1 kg), and year 1 to 3 (1.8 kg) and in SW from year 1 to 3 (0.6 kg); and percent body fat (%BF) increased in BB from year 1 to 3 (1.7%). There were no changes in SOC or TR. These results indicate that during their college careers, female collegiate athletes can be expected to maintain their %BF and athletes in sports like SW and VB can anticipate an increase in lean mass, but the increases may be less than many athletes, coaches, and trainers envision.